2006
DOI: 10.1111/j.1751-8369.2006.tb00150.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Landsat-7 satellite data and a DEM for the quantification of thermokarst-affected terrain types in the periglacial Lena?Anabar coastal lowland

Abstract: Extensive parts of Arctic permafrost‐dominated lowlands were affected by large‐scale permafrost degradation, mainly through Holocene thermokarst activity. The effect of thermokarst is nowadays observed in most periglacial lowlands of the Arctic. Since permafrost degradation is a consequence as well as a significant factor of global climate change, it is necessary to develop efficient methods for the quantification of its past and current magnitude. We developed a procedure for the quantification of periglacial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…According to Schirrmeister et al (2008) the stratigraphy of the permafrost sequences cropping out at the coast covers late Pleistocene and Holocene strata and is composed of less ice-rich fluvial silts and sands with peat layers, covered with 20-30 m thick ice-supersaturated silty to sandy Ice Complex deposits. Holocene thermokarst deposits have been found in alasses, thermoerosional valleys and in places discordantly superimposing the Ice Complex (Grosse et al, 2006). The hinterland of the coast is gently inclined towards the Laptev Sea in the north with a mean slope of 0.1 • and incised by a dendritic network of thermo-erosional valleys .…”
Section: Mamontov Klykmentioning
confidence: 97%
“…According to Schirrmeister et al (2008) the stratigraphy of the permafrost sequences cropping out at the coast covers late Pleistocene and Holocene strata and is composed of less ice-rich fluvial silts and sands with peat layers, covered with 20-30 m thick ice-supersaturated silty to sandy Ice Complex deposits. Holocene thermokarst deposits have been found in alasses, thermoerosional valleys and in places discordantly superimposing the Ice Complex (Grosse et al, 2006). The hinterland of the coast is gently inclined towards the Laptev Sea in the north with a mean slope of 0.1 • and incised by a dendritic network of thermo-erosional valleys .…”
Section: Mamontov Klykmentioning
confidence: 97%
“…Thermokarst in ice‐rich Yedoma expresses as large and partly coalesced basins with up to 40 m depth and several km width. According to remote sensing calculations about 50% of the Yedoma areas in the Siberian Laptev Sea lowlands are characterized by thermokarst depressions, and up to 80% of the area shows signs of permafrost degradation [ Grosse et al , 2006].…”
Section: Permafrost Degradation and Thermokarst On Earthmentioning
confidence: 99%
“…Their origin has been attributed to periglacial processes and permafrost degradation [e.g., Seibert and Kargel , 2001; Kuzmin and Zabalueva , 2003; Mangold , 2005; Soare et al , 2005a], but aeolian processes [ Soare et al , 2005b] and structural control [ Yoshikawa , 2003] have also been suggested. Our focus is on degradation features and their formation, and we compare the observations with our own field experience in Arctic Siberia as terrestrial reference [ Grosse et al , 2005, 2006, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Thermokarst lakes have mainly formed during the course of the Holocene and are a sign of local permafrost degradation following post glacial climate warming [ Rampton , 1988; Romanovskii et al , 2004; Walter et al , 2007]. Thermokarst lakes are abundant surface features across many high latitude regions, such as the Seward Peninsula [ Hopkins , 1949; West and Plug , 2008; Plug and West , 2009], the Arctic Coastal Plain [ Sellmann et al , 1975; Hinkel et al , 2005] as well as several areas in Interior Alaska [ Jorgenson and Osterkamp , 2005]; in Canada on Banks Island [ Harry and French , 1983], Tuktoyaktuk Peninsula [ Mackay , 1988], the Yukon Coastal Plain [ West and Plug , 2008; Plug and West , 2009], and Richards Island [ Burn , 2002], and in large regions of Siberia [ Romanovskii et al , 2004, Tomirdiaro and Ryabchun , 1973; Zimov et al , 1997; Smith et al , 2005; Grosse et al , 2006; Walter et al , 2007; Grosse et al , 2011]. While not all northern, high‐latitude lakes are of thermokarst origin [ Jorgenson and Shur , 2007; Smith et al , 2007], their importance to global climate change and northern high latitude soil and permafrost‐stored carbon cycling has been noted [ Zimov et al , 1997; Walter et al , 2006; Walter et al , 2007].…”
Section: Introductionmentioning
confidence: 99%